If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6+27+(-70)=0
We simplify the equation to the form, which is simple to understand
-6+27+(-70)=0
Remove unnecessary parentheses
-6+27-70=0
We move all terms containing to the left and all other terms to the right.
0=0+6-27+70
We simplify left and right side of the equation.
0=+49
0=49
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 5r^2=35r | | 5(f-8)=-40 | | 3x+12=28-5x | | 1-8x=-16x^2 | | 2b-c-a+4=0 | | 3+7lnx=38 | | 2b-a-c+4=0 | | -10(s+5)=-133 | | 2a-b-c+4=0 | | 7+12x=29+x | | -49=-2x+3(-2x+13) | | -10(s+5)=133 | | 54n^3-2000=0 | | -3x^2+6x=4 | | t-(-2)=-8 | | b+2c-4a+2=0 | | b+2a-4c+2=0 | | 4.2/3-1 | | 6(t+2)=0 | | 2(2b+6)=4b-8 | | 7|-1-3|= | | 5-3(3+5x)=71 | | 169=37x-16 | | -6+9-(-7)= | | -16x^2+144x=0 | | 6x-8=4x+22 | | y-9=-2/3x | | 1-7/5x3 | | 3/7-0 | | 2x=111 | | 4(a-2)=6(a+15) | | 4x^2-28x+149=5 |